1988
DOI: 10.1128/jcm.26.2.257-260.1988
|View full text |Cite
|
Sign up to set email alerts
|

High-content aminoglycoside disks for determining aminoglycoside-penicillin synergy against Enterococcus faecalis

Abstract: We investigated the use of high-content aminoglycoside disks for determining Enterococcus faecalis susceptibility to aminoglycoside-penicillin synergy. The susceptibility of the organisms to synergy was established by 24-h time-kill studies performed with streptomycin, kanamycin, amikacin, gentamicin, and tobramycin, alone and in combination with penicillin. A total of 20 isolates that were susceptible to all drug combinations and 20 strains that were resistant to each aminoglycoside-penicillin combination wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 13 publications
3
27
0
Order By: Relevance
“…There was complete agreement between disk diffusion and standard agar screen results, which is consistent with previously published studies (10,13,15). Although most resistant strains showed no inhibition zone, some resistant and susceptible isolates may give inhibition zones at or near the 10-mm breakpoint.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There was complete agreement between disk diffusion and standard agar screen results, which is consistent with previously published studies (10,13,15). Although most resistant strains showed no inhibition zone, some resistant and susceptible isolates may give inhibition zones at or near the 10-mm breakpoint.…”
Section: Discussionsupporting
confidence: 90%
“…(ii) High-content disk diffusion. Disks containing 120 ,ug of gentamicin and 300 ,ug of streptomycin were prepared at the UC Medical Center as described previously (13). The disks were used with Mueller-Hinton agar plates (Becton Dickinson Microbiology Systems) to perform disk diffusion testing by recommended guidelines (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We streaked a heavy unquantitated inoculum onto brain heart infusion agar with 1,000 tig of gentamicin per ml and .17 MHA 198 Disks were 6 mm in diameter. b HLR was defined as a MIC of >2,000 ,ug/ml, as resistance to synergism, as resistant by one of several other techniques, or a combination of these (177,180,198 2,000 pLg of streptomycin per ml and found that all strains that grew, even with only a few colonies, had HLR as confirmed by MIC. For those strains that did not grow, antibiotic MICs were <1,000 pLg of gentamicin per ml or <2,000 Vag of streptomycin per ml (135, 152; unpublished observations).…”
Section: Screening Tests For High-level Aminoglycoside Resistancementioning
confidence: 99%
“…However, lack of synergy both in vivo and in vitro is seen when E. faecalis strains express high-level (MIC 2 2000 mg/l) aminoglycoside resistance, a characteristic which is occurring with increasing frequency worldwide (4,6,8,12). Laboratory detection of high-level E. faecalis resistance is therefore of importance and can readily be performed using the disk diffusion method with high potency (gentamicin 120 pg) disks (14,15,16,19). The 10 pg gentamicin disk used for routine susceptibility testing in many countries cannot predict high-level resistance since strains with normal low-level resistance often fail to produce zones of inhibition (14,15).…”
mentioning
confidence: 99%